IMPROVING VOCABULARY MASTERY THROUGH CROSSWORD PUZZLE - Mansur, Nurfauziah; Fatima; Zulfikri, Zulfikri (Datokarama English Education Journal, 2023)
This research aims at finding out the use of crossword puzzle in improving vocabulary mastery at seven grade students of SMP Negeri 10 Palu. This research applied a quasi-experimental design, in which there were two groups, an experimental and a control group. Seven grade E was the experimental group, while seven grade F was the control group. This research involved 50 students of SMP Negeri 10 Palu. The samples of this research were taken from the population of grade seven students by using a purposive sampling technique. The researcher used tests as the instrument for collecting data. The tests were divided into two; pre-test and post-test which were given to the experimental and control group. The treatment was conducted six times and was given to the experimental group by using a crossword puzzle, while the control group used the other technique. The data obtained from the test were analysed statistically. From the analysis, there was a difference between the achievement of the experimental (85.5) and the control group (44.2). It was based on the hypothesis testing done, by using 0.05 level of significance and 48 degrees of freedom (df), the researcher found that t-counted (6.08) is higher than t-table (2.0126). It means that the hypothesis (Ha) is accepted or in other words, the use of crossword puzzles has a significant effect on students’ learning outcomes in learning vocabulary.